Book Reviews (Journal of Contemporary Studies, 2025)
1.The Challenge of Enlightenment, Conflict Transformation, and Peace in Pakistan2. Sri Lanka’s Easter Sunday Massacre: Lessons for International Community3. Realism: A Distinctively 20th Century European Tradition (Trends in European IR theory)4. Islamic Perspectives on International Conflict Resolution: Theological Debates and the Israel-Palestinian Peace Process